V1504 CYG: OUTBURSTS - Pavlenko, E. P.; Berezina, E. (Одеські астрономічні публікації, 2007)
The behavior of the dwarf nova V1504 Cyg during 2007 superoutburst and during several normal outbursts is considered. The binary during normal outbursts shows loop-like tracks on the V, V-R diagram, where prior the superoutburst the loop is steep and narrow while after the superoutburst the loop is mildly sloping and wider. The loop of the superoutburst resembles those of normal outbursts precedings the superoutburst. V1504 Cyg displays the early superhumps phenomenon during the ricing branch and first few days of the superoutburst.